Light regulates tropical symbiotic nitrogen fixation more strongly than soil nitrogen. (September 2018) - Taylor, Benton; Menge, Duncan
Abstract Nitrogen limits primary production in almost every biome on Earth1, 2 . Symbiotic nitrogen fixation, conducted by certain angiosperms and their endosymbiotic bacteria, is the largest potential natural source of new nitrogen into the biosphere3, influencing global primary production, carbon sequestration and element cycling. Because symbiotic nitrogen fixation represents an alternative to soil nitrogen uptake, much of the work on symbiotic nitrogen fixation regulation has focused on soil nitrogen availability4–8 . However, because symbiotic nitrogen fixation is an energetically expensive process9, light availability to the plant may also regulate symbiotic nitrogen fixation rates10, 11 . Despite the importance of symbiotic nitrogen fixation to biosphere functioning, the environmental factors that most strongly regulate this process remain unresolved. Here we show that light regulates symbiotic nitrogen fixation more strongly than does soil nitrogen and that light mediates the response of symbiotic nitrogen fixation to soil nitrogen availability. In a shadehouse experiment, low light levels (comparable with forest understories) completely shut down symbiotic nitrogen fixation, whereas soil nitrogen levels that far exceeded plant demand did not fully downregulate symbiotic nitrogen fixation at high light. For in situ forest seedlings, light was a notable predictor of symbiotic nitrogen fixation activity, but soil-extractable nitrogen was not. Light as a primary regulator of symbiotic nitrogen fixation is a departure from decades of focus on soil nitrogen availability. This shift in our understanding of symbiotic nitrogen fixation regulation can resolve a long-standing biogeochemical paradox12, and it will improve our ability to predict how symbiotic nitrogen fixation will fuel the global forest carbon sink and respond to human alteration of the global nitrogen cycle. Symbiotic nitrogen fixation is one of the most important sources of nitrogen in terrestrial ecosystems. In this study, the researchers demonstrate that light availability is an outstanding driver of symbiotic nitrogen fixation in tropical leguminous trees.